The role and importance of the small business sector in the economic development of the Mazowieckie Province - Kozak, Sylwester (Management and Administration Journal, 2019)
The goal of the study is the examination of the impact of the small business sector on thelocal economic growth in the Mazowieckie Province. The research proves that the increase in thenumbers of operating and newly registered small enterprises contributes positively to the countyeconomic development measured with the total value and the per capita value of traded productiongenerated by locally operating enterprises, as well as the number of their employees. Additionally theincrease in realized capital expenditures and the province GDP positively impact the county’s economicdevelopment. The study is based on data from the Local Data Bank of GUS and covers allcounties (excluding the capital city of Warsaw) in the province during the period 2003-2014.